2016
DOI: 10.1002/jcp.25291
|View full text |Cite
|
Sign up to set email alerts
|

Let-7d miRNA Shows Both Antioncogenic and Oncogenic Functions in Osteosarcoma-Derived 3AB-OS Cancer Stem Cells

Abstract: Osteosarcoma (OS), an aggressive highly invasive and metastatic bone-malignancy, shows therapy resistance and recurrence, two features that likely depend on cancer stem cells (CSCs), which hold both self-renewing and malignant potential. So, effective anticancer therapies against OS should specifically target and destroy CSCs. We previously found that the let-7d microRNA was downregulated in the 3AB-OS-CSCs, derived from the human OS-MG63 cells. Here, we aimed to assess whether let-7d modulation affected tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…Direct targets of let-7 include oncogenes such as RAS and HMGA2 [23,32]. In the present study, we found expression of let-7d was lower in breast cancer tissue than in normal breast tissue.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Direct targets of let-7 include oncogenes such as RAS and HMGA2 [23,32]. In the present study, we found expression of let-7d was lower in breast cancer tissue than in normal breast tissue.…”
Section: Discussionmentioning
confidence: 45%
“…On the other hand, let-7d contributes to the pathogenesis of some cancers. For instance, it was reported that let-7d exerted both anti-oncogenic and oncogenic effects in osteosarcoma [23]. Besides this, let-7d directly targeted CCL7, COL3A1, HMGA2 [23], and PBX3 [24,25], and inhibited cell growth, invasion, and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still difficult to solve the two major problems, the recurrence and metastasis. Approximately 80–90% of the causes of death in patients with osteosarcoma are metastasis especially pulmonary metastasis (13). Therefore, it is extremely urgent to find effective early diagnostic tools and treatment in osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are proved to be related to the occurrence and the metastasis of osteosarcoma (13). miRNA expression in tumor cell lines and different clinical osteosarcoma samples were investigated and 22 differentially expressed miRNAs were found, among them the miRNAs miR-135b, miR-150, miR-542–5p and miR-652 have been verified and confirmed that may be involved in the tumor genesis of osteosarcoma (1).…”
Section: Introductionmentioning
confidence: 99%
“…Almost 80%-90% of patients died due to pulmonary metastasis. [2][3][4] Therefore, it is urgent to understand the molecular mechanism of metastasis and find an effective therapeutic target to inhibit cancer cells' metastasis.…”
Section: Introductionmentioning
confidence: 99%